Building bridges through science - Lissek, Thomas; Bading, Hilmar; Draguhn, Andreas; Grinevich, Valéry; Koehr, Georg; Spanagel, Rainer (Neuron, 2017)
Science is ideally suited to connect people from different cultures and thereby foster mutual understanding. To promote international life science collaboration, we have launched “The Science Bridge” initiative. Our current project focuses on partnership between Western and Middle Eastern neuroscience communities.
Available online 15 November 2017
Gesehen am 27.06.2018